PENGARUH KUALITAS PELAYANAN ASURANSI JIWA PT. PRUDENTIAL LIFE ASSURANCE TERHADAP KEPERCAYAAN (TRUST) NASABAH DI KOTA PEKANBARU - Saur Pertiwi Pasaribu; Mita Rosaliza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Customer trust can be achieved through a service process, in which there is a process of fulfillment customer needs. This research was conducted at PT. Prudential Life Assurance Pekanbaru, be function for knowing the level quality of customer service, the level of customer trust, and the influence of service quality toward customer trust in PT. Prudential Life Assurance Pekanbaru. This research use descriptive quantitative research methods. Source of this data is from filling out questionnaires by respondents. Analysis data technic used in this research is descriptive analysis and quantitative analysis, and the data were analyzed using the SPSS program. This research using technique Simple Random Sampling. The sample used in this study amounted to 95 people. Result showed that tangible, reliability, responsiveness, and empathy has affect on customer trust. This is evidenced by the value of t count> t table (10.951> 1.985) and Significance <0.05 (0.000 <0.05). Value (R2) is 0.563 which means 56.3% empathy, reliability, assurance, responsiveness and tangible affect the level of customer trust in PT. Prudential Life Assurance Pekanbaru, while the remaining (100% - 56.3% = 43.7%) is influenced by other factors which was not examined in this study.Keywords: Service Quality, Customer Trust